Stakeholders and Farmers’ Preferences Towards Contract Attributes: Evidence from Hybrid Maize Production in Indonesia - Destu Syah Inanda; Pandu Laksono; Any Suryantini; Arini Wahyu Utami (Caraka Tani: Journal of Sustainable Agriculture, 2025)
The availability of quality seeds is critical to supporting the sustainability of agriculture, which is further reinforced by the success of contract farming between seed companies and partner farmers. To foster a mutually beneficial partnership, it is essential to align the needs of farmers with the facilities and services provided by the company through well-defined contract terms and conditions. This study aims to explore the contract attribute preferences and their importance levels among farmers, growth leaders, and companies using a quantitative approach. A discrete choice experiment utilizing the conditional logit model was employed to investigate the preferences of 170 farmers, while a descriptive analysis was used to outline the preferences of other stakeholders. The findings indicate that farmers prefer written agreements over informal ones, favor shorter contract durations, and demand higher prices. Additionally, farmers showed a marked preference for receiving inputs, incentives, and credits. The preference patterns of stakeholders align with those of farmers regarding agreement form, inputs, price, incentives, and credit, although stakeholders tend to favor contracts with longer durations. Based on the rank-based quotient method, both growth leaders and farmers identified price, input subsidies, incentives, credits, agreement form, and duration as the most important attributes in maize seed partnership contracts, in descending order of importance. Contrarily, the company prioritizes input subsidies over other attributes, including price, duration, credit, incentive, and agreement form. These insights can inform the design of more suitable and effective contracts, thereby fostering sustainable partnership relationships in the future.